The Effect of High School Accounting Study on Self-Efficacy: An Empirical Study on Students Enrolled in an Introductory Tertiary Accounting Course - Choo, Nicolas (Auckland University of Technology, 2020)
Self-efficacy is defined as the convictions of individuals that they can accomplish a particular task (Bandura, 1977a). Prior research has found that self-efficacy can help students perform better academically (Beatson, Berg, & Smith, 2019). If prior knowledge could affect a student’s self-efficacy, it could indirectly lead to students achieving better grades. This study investigated whether prior accounting knowledge gained from the study of accounting at high school would affect a student’s self-efficacy when they undertook an introductory tertiary accounting course. Student responses were captured through an anonymous survey, and this research had a sample size of 272 respondents. This research used regression analyses to compare the self-efficacy of respondents who had studied accounting at high school and those who did not do so. Prior knowledge is represented by three proxies in this research: i.e. the presence or absence of prior knowledge gained from the study of accounting at high school (PK), the highest level of any accounting syllabi studied at high school (HL), and the type of accounting syllabi studied at high school (AS). This research found that there was no significant difference in self-efficacy levels between students who had studied accounting at high school and those who did not do so. The results were similar for all proxies of prior knowledge (i.e. PK, HL, and AS). These results refuted anecdotal accounts that studying accounting at high school would make one more confident when studying the subject at a tertiary level. The possible explanations for these results are the difference in between university and high school accounting syllabi, the presence of alternate factors that could be a better predictor of self-efficacy (i.e. prior results), the potential impact of other sources of self-efficacy besides enactive mastery experiences (i.e. vicarious experiences, verbal persuasion and physiological states), or even the type of self-efficacy scales used in the research. The implication of the research is that high school teachers, lecturers and career counsellors should not discourage students from studying accounting at university on the basis that they did not study the subject at high school. However, the limitation of this study is that it may not be representative of the students enrolled in the introductory tertiary accounting course in terms of ethnicity. Besides that, there were also no students who studied one type of accounting syllabi, i.e. International Baccalaureate (IB).
Keywords: Prior knowledge; Self-efficacy; High school; Introductory tertiary accounting course